TAREKAT QA - Cholil, Muhammad (Dialogia: Jurnal Studi Islam dan Sosial, 2015)
Abstract: The term of tarekat in Islamic study is widely known in various circles. Especially in recent years, many congregations have sprung up one after the other meets Islamic studies. One of the most famous institutes is Qa>diriyah wa Naqshabandiyah. This tarekat has spread too many regions both within the general public and at Islamic boarding school. Islamic boarding school which is the framework of Islamic education system, in which there are classic teaching models belonging salafi, by learning Islamic classical words and deepening of Sufism, as well as boarding school founded by Sheikh Imam Muhadi named "Manbaul 'Adhim". This boarding school has a tradition like salafiyah such other boarding schools. However, with the emergence of Qa>diriyah wa Naqshabandiyah, then these schools identify themselves with tarekat that they followed. Thus, Qa>diriyah wa Naqshabandiyah often replace Islamic Boarding School Manbaul 'Adhim. The spirit of this congregation becomes a motivator in spreading his teachings around them. This article was written in order to know about the nature of the growing congregation in Islamic society, namely Qa>dariyah wa Naqshabandiyah and influence especially among schools. Keywords: Tarekat Qadiriyah Naqshabandiyah, Bai’atan, dan Pesantren Manbaul ‘Adhim